Characteristics of hurricane-induced wind, wave, and storm surge maxima along the U.S. Atlantic coast. (May 2020) - Qiao, C.; Myers, A.T.; Arwade, S.R.
Abstract: Hurricanes induce multiple hazards including high wind speeds, large waves, and storm surge. The characteristics of these hazards have an important effect on the design of offshore structures and determine the suitability of simplifying assumptions for modeling, such as whether the maxima can be reasonably modeled as occurring simultaneously during the hurricane and whether the N -year values of the hazards can be modeled separately and combined. Such assumptions are common in practice. Assessing the implications of these assumptions to better inform hazard modeling along the U.S. Atlantic coast is the central objective of this paper. To this end, the characteristics of wind speeds, waves, and storm surge during hurricanes are evaluated for ten areas where development of offshore wind is proposed. The assumptions are evaluated for a model of an offshore wind turbine using time histories of hazards during intense hurricanes and using so-called environmental contours constructed through a novel implementation of the Inverse First Order Reliability Method. The results of this study show that these assumptions are reasonably accurate, especially for wind and wave in shallow waters and for wind and surge in deep waters. Hazard ratios are proposed as a suitable representation of the characteristics of hazard maxima. Highlights: Metocean conditions are simulated for a 100, 000-year synthetic hurricane catalog. Evaluated the assumption of simultaneous hazard maxima during the hurricanes. Evaluated the assumption of N-year hazards occur at the same hurricane. A novel implementation of the IFORM to improve efficiency and accuracy.